THEORETICAL AND METHODOLOGICAL BASIS OF ADVANCED PROFESSIONAL TRAINING FOR SECONDARY VOCATIONAL EDUCATION SPECIALISTS - Palyanov, Mikhail; Mavrina, Irina; Olga; Ovchinnokov, Vladislav; Pokhorukov, Oleg; Churekova, Tatiana (Revista Inclusiones, 2020)
The relevance of the study lies in the importance of adopting innovative solutions for further evolution of the Russian System of SVE. The article is aimed at the development of theoretical and methodological grounds for advanced professional training of SVE specialists. The creation of educational and production clusters will provide professional resources for SVE organizations, resulting in the advanced approach in the vocational training in interaction with social partners. Using the comparison method, the study analyzes the experience of implementing public-private partnership programs in the sphere of SVE in Russia. The analysis revealed that the motivation of social partners to interact with vocational education institutions increases with the competition growth and is considered as a way to diversify production and business risks, as well as to reduce the costs for personnel training (retraining, advanced training). The analysis of the educational and production clusters functioning experience in experimental sites of leading educational organizations of SVE in the Siberian Federal District made it possible to identify and describe wide changes in the system of SVE, stages of implementing the mechanism for creating the system of advanced professional training for specialists with SVE, educational technologies required to organize the educational and production process, as well as conditions for the creation and implementation of the complete educational and production process in the SVE system.